2021
DOI: 10.1093/advances/nmab034
|View full text |Cite
|
Sign up to set email alerts
|

Protein Intake from Birth to 2 Years and Obesity Outcomes in Later Childhood and Adolescence: A Systematic Review of Prospective Cohort Studies

Abstract: Emerging evidence shows an association between protein intake during infancy and later obesity risk, and that association may differ by protein sources. This systematic review summarized and evaluated prospective cohort studies assessing the long-term association of total protein intake and protein sources during infancy (from birth to 2 y) with subsequent obesity outcomes in childhood or adolescence. Literature searches were conducted in Embase, Medline, Scopus, and Web of Science. Sixteen studies that report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 47 publications
3
15
0
2
Order By: Relevance
“…More recently, Stokes et al reviewed the association between protein intake in infants and children up to 2 years of age and childhood obesity-related outcomes in a systematic review including only prospective cohort studies ( 8 ). Several studies included in this review were also included by Stokes et al ( 30 32 , 34 , 35 , 38 42 , 45 , 46 , 48 ), and they performed a meta-analysis on total protein intake and BMI with three of the five studies included in our meta-analysis, obtaining similar results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Stokes et al reviewed the association between protein intake in infants and children up to 2 years of age and childhood obesity-related outcomes in a systematic review including only prospective cohort studies ( 8 ). Several studies included in this review were also included by Stokes et al ( 30 32 , 34 , 35 , 38 42 , 45 , 46 , 48 ), and they performed a meta-analysis on total protein intake and BMI with three of the five studies included in our meta-analysis, obtaining similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Although an adequate amount and quality of dietary protein is crucial for growth, a very high-protein diet in infancy may accelerate growth and increase the likelihood of overweight and obesity in childhood and later in life (4)(5)(6)(7)(8). A systematic review of the Nordic Nutrition Recommendations (NNRs) for 2012 revealed that there was convincing evidence for an effect of higher protein intake in infancy and early childhood on increased growth and higher body mass index (BMI) later in childhood (5).…”
mentioning
confidence: 99%
“…Several original studies indicated that high protein formula can result in accelerated weight gain, higher BMI, and increased body-fat, which in turn, exacerbate the risk of adulthood obesity [ 66 87 89 90 98 99 ]. The results of these studies have recently been validated by meta-analyses, which reached the same conclusion [ 91 92 ]. With rates of childhood obesity continuing to increase, early metabolic programming is becoming an area of interest for researchers in the field [ 66 ].…”
Section: Discussionmentioning
confidence: 69%
“…Recent meta-analyses support the data from these original studies, with both Pimpin et al [ 91 ] and Stokes et al [ 92 ] confirming a positive association between high protein intake in the early years and increased weight gain/higher BMI in the months and years that follow. The first of these analyses compared the effects of high protein formula with low protein formula across 24 studies.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation